Lived Experience of Student Teenage Mothers in Higher Learning Institutions in Dar es Salaam, Tanzania: Drives, Challenges and Support Systems - Regina M. Maunde (Eastern African Journal of Humanities and Social Sciences)
This article explores the lived experiences of student teenage mothers in higher learning institutions in Dar es Salaam, Tanzania. It specifically analyses the factors behind their drive for higher education, the challenges they face, and the support systems available for them. Data were collected by interviewing a sample of twenty (20) student teenage mothers from The Mwalimu Nyerere Memorial Academy (MNMA) and doing a documentary review. The data were analysed by using content analysis methods based on the Self-Determination Theory. The findings show that various factors drive student teenage mothers to carry on with their pursuit of career education, including empowerment and independence, improved career forecasts and networking, and social connection. However, they face several challenges which can be grouped into three namely: financial challenges, psychological challenges, and challenges related to balancing between academic and parenting duties. The article finally explains the support systems such as counseling and guidance, mentorship, childcare services, and community and peer support.